Evaluation of the relationship between portal vein diameter and colorectal liver metastases on computed tomography - Karatay, Emrah; Laçin, Şahin; Eren, Abdulkadir (My University, 2024)
Background/Aim: The most common and often first metastatic site of colorectal cancer (CRC) is the liver, and radiological modalities have a critical role in the diagnosis of colorectal liver metastasis (CRLM). In this study, the possible relationship between portal vein diameter, number of metastases, and metastasis diameter was evaluated in CRLM patients who underwent computed tomography (CT) examination with intravenous contrast (IV). Patients and Methods: Cases diagnosed with CRLM who underwent abdominal CT examination with IV contrast between December 2020 and January 2024 were retrospectively scanned. People over the age of 18 were included, and cases were divided into three subgroups according to the number of metastases: a (single), b (two), and c (three and/or more). Results: There were 101 male and 74 female cases; the youngest case was 39 (male) and the oldest case was 87 (male) years old. According to the number of CRLMs, group a had 47 cases, group b had 23, and group c had 105 cases. The minimum diameter of metastasis was 0.74 cm, the maximum was 11.86 cm, and the mean diameter was 4.45±2.67 cm. There was a significant correlation between the presence of metastasis in the left lobe and the diameter of the metastases (p<0.05). Conclusion: The relationship between portal vein diameter and CRLM using contrast-enhanced CT scans was explored. While no significant correlation was found between portal vein diameters and metastasis size, a notable association was observed between metastasis size and their presence in the left liver lobe. These findings suggest that CRLMs in the left lobe may respond better to preoperative chemotherapy and surgical interventions. This novel insight could help develop targeted treatment strategies for CRLM, though further research with larger cohorts is needed.
Keywords: Colorectal Cancer; Computed Tomography; Liver Metastasis; Metastasis Diameter; Portal Vein